Textural optimisation of fish-gelatine stingless bee honey gummies by response surface methodology - Muzafar, Muhammad Mujahid Danial; Zakaria, Siti Aisyah Najwa; Mohd Rus, Shaiqah; Salleh, Mohd Syahmi; Haris @ Harith, Muhammad Salahuddin (IIUM Press, 2026)
Due to concerns over the halal status of gelatine traditionally derived from porcine and bovine sources, the demand for halal-certified alternatives is growing that ensure authenticity and meet dietary requirements, particularly in the gummy industry. Developing this product not only embrace the cultural and religious requirements but also expands the opportunities for the pharmaceutical applications in delivering nutraceutical ingredients. The present work aimed to investigate the effect of starch, fish gelatine and stingless bee honey (SBH) and to optimise their concentration using Response Surface Methodology (RSM) for a formulation that meets target criteria of balanced springiness, cohesiveness, and minimised hardness suitable for halal-certified gummy products. Response Surface Methodology (RSM) with a Central Composite Design (CCD) was employed to optimise. Gummies were prepared using a cold mixing technique then followed by textural analysis, pH value determination, storage stability testing, and microbiological testing. The study factors used were starch (15-25 g), fish gelatine (35-45 g) and (SBH 20-30 g) with 18 experimental runs. The runs included 4 centre points, and the targeted responses were springiness (0.9–1.2 mm, goal 1.04 mm), cohesiveness (0.9–1.14, goal 0.98), and hardness (31–107.7 g, minimised) to satisfy the market standards for gummy texture. For cohesiveness (significant model, p = 0.0021 with critical interaction factors AC and quadratic terms A and B significant), hardness (significant model, p = 0.0333; fish gelatine significant, p = 0.007), the fitted models were quadratic. In contrast, the springiness model (non-significant, p = 0.2923). The springiness was considered only as observe texture attribute rather than a primary optimisation target. The optimised formulation (15 starch, 37 fish gelatine, and 25 SBH) was validated, the predicted and actual values closely matched, with only slight variations (hardness deviation within acceptable limits, cohesiveness error ~0.25%, and springiness error ~2.2%). Preliminary storage stability testing over 14 days’ period showed the gummies maintained the textural quality. Microbiological evaluation demonstrated no growth of mould and bacterial also maintained the product safety. These findings showed that RSM with CCD can guide the formulation of fish gelatine and SBH-based gummies to achieve desirable cohesiveness and hardness while preserving the safety and texture gummies features